SELF-EFFICACY AND DIETARY ADHERENCE IN PATIENT WITH DIABETES MELLITUS: A CROSS SECTIONAL STUDY - Kause, Serli; Dee, Theodehild M. Theresia; K. Lette, Priska (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Diabetes mellitus is a non-communicable disease with a steadily increasing prevalence. Diet management plays an pivotal role in controlling blood glucose and preventing complications, but patient compliance still varies. Self-efficacy is a major factor that influences the success of diet management. The purpose of this study is to investigate the correlation between self-efficacy and dietary management in individuals with diabetes mellitus. A descriptive cross-sectional study was conducted from March to April 2024 involving 181 respondents within the working area of Pasie Panjang Public Health Center. Data were analyzed using the Spearmen rank correlation test. The finding showed that 36.5% of patients had moderate self-efficacy, while 51.4% had high dietary compliance. There was a significant relationship between self-efficacy and diet adherence (p=0.000; r=0.785), indicating a strong correlation. Individuals with high self-efficacy tended to be more compliant in following their diet, while low self-efficacy was associated with low diet adherence. Thus, increasing self-efficacy needs to be a focus in interventions to improve diet compliance in individuals with diabetes mellitus